THE EFFECT OF MUDHARABAH, MURABAHAH AND INTEREST RATE FINANCING ON NET PROFIL IN BUKOPIN ISLAMIC BANKS THE PERIOD 2016-2019 - Wirman Wirman; Syifa Nurizkiana (Imara: JURNAL RISET EKONOMI ISLAM, 2021)
This study aims to determine the effectS of mudharabah, murabahah and interest rate financingon net profit of Bukopin Sharia Banks in the period of 2016- 2019 . This type of research is quantitativedescriptive using secondary data obtained from the Bukopin Sharia Bank's official website. This study usessaturated sampling in determining samples. The statistical method used is descriptive analysis, classicassumption test (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test),multiple linear regression analysis, hypothesis testing (T test and f test) and the coefficient of determination.The results of this study shows partially mudharabah financing has a significant negative effect on netprofit, murabahah financing has a significant positive effect on net profit, and interest rate has no effecton net profit. While simultaneously mudharabah, murabahah and interest rate financing affect net profit.